2021
DOI: 10.1186/s12879-021-06116-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between extreme temperature and pulmonary tuberculosis in Shandong Province, China, 2005–2016: a mixed method evaluation

Abstract: Background The effects of extreme temperature on infectious diseases are complex and far-reaching. There are few studies to access the relationship of pulmonary tuberculosis (PTB) with extreme temperature. The study aimed to identify whether there was association between extreme temperature and the reported morbidity of PTB in Shandong Province, China, from 2005 to 2016. Methods A generalized additive model (GAM) was firstly conducted to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(55 reference statements)
3
5
0
Order By: Relevance
“…Rao et al ( 2016 ) found that areas with low temperature tended to have higher TB incidences in Qinghai province of China. Based on the total population data analysis, we found that high temperature produced a protective effect on TB transmission in Kashgar city, which was consistent with some studies; Chen et al ( 2021 ) found that extreme high temperature has significantly decreased the risk of PTB at the provincial levels. However, some literatures also reported high temperature as a risk factor of TB transmission; for example, Onozuka and Hagihara ( 2015 ) revealed that the occurrence of extreme heat temperature events resulted in a significant increase in the number of TB cases in Fukuoka, Japan, which seems to vary from place to place as the effect on TB incidence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Rao et al ( 2016 ) found that areas with low temperature tended to have higher TB incidences in Qinghai province of China. Based on the total population data analysis, we found that high temperature produced a protective effect on TB transmission in Kashgar city, which was consistent with some studies; Chen et al ( 2021 ) found that extreme high temperature has significantly decreased the risk of PTB at the provincial levels. However, some literatures also reported high temperature as a risk factor of TB transmission; for example, Onozuka and Hagihara ( 2015 ) revealed that the occurrence of extreme heat temperature events resulted in a significant increase in the number of TB cases in Fukuoka, Japan, which seems to vary from place to place as the effect on TB incidence.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have demonstrated that abnormal changes in climate can lead to significant variations in the incidence and geographical distribution of infectious diseases, accompanied with serious adverse effects on human health. Due to the diversity in the natural environment, ecological characteristics, meteorological types, population immunity, and other social factors, the impact of meteorological factors on diseases from different studies also varied (Li et al 2021 ; Chen et al 2021 ; Maharjan et al 2021 ; Kirolos et al 2021 ; Desikan et al 2019 ; Onozuka and Hagihara 2015 ; Allen and Sheridan 2018 ; Feng et al 2021 ; Kim et al 2019 ). The incidence of TB in Kashgar city is high.…”
Section: Introductionmentioning
confidence: 99%
“…With higher RR values at a lag of 4 days for all groups, and in the discussion stratified by gender, the RR of developing TB reached its maximum at lag 21 days, − 15 °C for the male and female groups, which were respectively reported as 2.00, 95% CI (0.68–5.82) and 2.40, 95% CI (0.78–7.36), respectively; in the discussion stratified by age, the RR reached its maximum at lag 21 days, − 15 °C in the 36–64 and ≥ 65 age groups, reported as 2.58, 95% CI (0.84–7.96) and 1.99, 95% CI (0.65–6.09), respectively, and in the ≤ 35 age group at lag 4 days, -15℃ had the greatest RR, reported as 2.00, 95% CI (1.13–3.57). High temperatures were protective against TB transmission, this is in line with the findings noted by Chen et al that extreme heat was associated with reduced PTB risk (RR = 0.982, 95% CI:0.966–0.998) 28 . The cumulative effect of hypothermia reached its maximum at lag 21 days, and the susceptibility of males was significantly higher than that of the female population, which may be attributed to the fact that males are the backbone of all sectors of society, have a lot of social engagements, and are more susceptible to TB because of the higher frequency of smoking and alcohol consumption and lack of physical exercise 29 .…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Chen et al adopted the correlation number to explore the effect of extreme temperature on PTB. As revealed by the results, the effect of extreme temperature on PTB was different in different regions ( 15 ). However, few people have investigated the effect of extreme humidity and extreme wind speed on PTB.…”
Section: Introductionmentioning
confidence: 90%